Agile ageing – A modifiable vital sign to mitigate the risk of falls in older adults?. (March 2021) - Ogilvie, Madeleine; Wallen, Matthew P.; Talpey, Scott W.
Abstract: Falls prevention in older adults is a targeted priority because a fall can lead to disability, institutionalisation and presents a signficant financial burden. Falls are multifactoral in nature however, impairments in both physical and cognitive functioning have been linked to their occurrence. Currently, testing and exercise training for falls prevention focuses on physical qualities such as balance and strength. Agility is a unique physical quality that couples an individuals perceptual cognitive ability with the ability to produce a quick and accurate movement. Agility is relatively well understood in a sporting context however, its application to falls prevention has been minimal. Because a fall may occur while an individual is perceiving information from the dynamic environment around them while attempting to execute a rapid and accurate movement it is hypothesised that concepts and methods used to assess and train agility in athlete populations can be use to improve practices related to the screening and training to mitigate the risk of a fall in an older adult.